Difference Between the Profiles Presented by Yeasts that Colonize the Vaginal Mucosa or Cause Primary or Recurrent Candidiasis - Moreira, D.; Ruiz, L. S.; Leite-Jr, D. P.; Auler, M. E.; Ramos, R. T.B.; Costa, V. T.; Lara, B. R. [UNESP]; Gasparetto, A.; Gandra, R. F.; Melhem, M. S.C.; Paula, C. R. (Springer Nature, 2021)
Candida yeasts are the most frequent in the vaginal content. This yeast may be a normal microbiota but also causes candidiasis. In symptomatic cases, primary candidiasis (VVC) or recurrence (RVVC) can be considered. This study aims to compare the frequency and in vitro sensitivity profile of Candida species isolated in the vaginal content with the different stages of the presence of yeasts. A total of 258 non-pregnant patients with/without VVC were prospectively screened at a teaching Health Centre of the Faculty of Medicine, in the University of Sao Paulo. The vaginal isolates were identified by traditional and molecular methods. Yeasts were isolated in 160 women. 34% were asymptomatic, 34% with vulvovaginal candidiasis (VVC), and 32% recurrent vulvovaginal candidiasis (RVVC). C. albicans was the most frequent species with 50.1% (82/160), followed by C. parapsilosis 13.7%(22/160), C. glabrata 12.5% (20/160), and C. tropicalis (6.2%). Analysis by the group showed that, in the asymptomatic group, eight yeast species were isolated, C. albicans 44.5% (24/54), C. glabrata 20% (11/54), C. parapsilosis and Rhodotorula rubra being the most frequent. In the VVC group, 11 yeast species were identified. Most isolates were C. albicans 68.5% (37/54), C. tropicalis 7.5% (4/54), and C. parapsilosis 5.5% (3/54). In the RVVC group, ten species were identified, the most frequent being C. albicans 38.5% (20/52), C. parapsilosis 17% (9/52), C. glabrata 4% (8/52), and C. tropicalis 6% (3/52). Less frequent species, such as C. haemulonii and Trichosporon spp, were isolated in the VVC and RVVC groups, C. kefyr was isolated in the three groups studied, and Rhodotorula spp was isolated in the control and RVVC groups. Candida metapsilosis was present in two isolates from the RVVC group. Most isolates were considered sensitive to the tested antifungals. Less sensitivity was seen for caspofungin. In this study, we were able to verify that the most common species of yeasts found in vaginal secretion were isolated in the three groups studied; however, there was the diversity of species in VVC and RVVC. Cryptic species C. haemulonii and were isolated in symptomatic patients. High levels of MICs, some of the antifungals tested, in the control group, draw attention in the group of asymptomatic women. We would like to emphasize that this research aims to assist clinicians and gynecologists, as well as assist in the epidemiological studies of candidiasis, in our country, how to draw attention to the profile of sensitivity/resistance to antifungals.
Keywords: Candidiasis; DNA sequencing; Epidemiology; Microbiology; Vulvovaginal